Passionate Descartes: A reinterpretation of the body's role in Cartesian thought - Raga Rosaleny, Vicente, 1977- (2020)
Abstract The usual reading of Descartes' “anthropological” perspective classifies it as a radical dualism with a distinction between two substances, mind and body, which experience major interaction difficulties. Through a contextualization of Descartes' physiological and psychological thought as well as through a less fragmented reading of his work, we intend to review this traditional interpretation, thereby showing its distorted character. When we pay attention to passion, a new Descartes’ image as a sort of phenomenal monism appears, which is markedly different from the legendary image typically associated with him, even today.
Keywords: Descartes, René; Dualismo; Filosofía